Integrating father involvement into early childhood initiatives delivered at scale: key considerations - Nair, Sapna; Sinha, Harshula; Holding, Penny (Frontiers in Public Health, 2023)
Early child development (ECD) interventions, usually centred around the mother, exclude fathers from contributing to childcare.Research shows that a father's involvement in childcare can have a positive impact on the child's growth. In this light, a trial was conducted in rural India wherein a new programme component aimed at enhancing fathers' engagement in early child was incorporated into an existing childcare intervention. The paper highlights the learnings drawn from the trial to present pathways to change, that is, strategies needed to embed father involvement as a component within the intervention ecosystem.We take forward the exploration of the evidence to landscape father involvement in the childcare paradigm in India. We reflect on the experience of our earlier initiative and endeavor to understand the efforts of other practitioners as we critically evaluate potential next steps in scaling the integration of fathers into the ICDS, and other similar programs.